2017
DOI: 10.2105/ajph.2016.303630a
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Cardiovascular Disease in Sexual Minorities

Abstract: Background: Mental health and HIV disparities are well documented among sexual minorities, but there is a dearth of research on other chronic conditions. Cardiovascular disease remains the leading cause of death worldwide. Although sexual minorities have high rates of several modifiable risk factors for cardiovascular disease (including stress, tobacco use, and alcohol consumption), there is a paucity of research in this area. Objectives: In this systematic review, we synthesized and critiqued the existing ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 0 publications
6
88
1
1
Order By: Relevance
“…There are likely a variety of factors influencing this growth, such as the increasing visibility in popular culture of individuals that are neither hetero- nor homosexual (e.g., pop stars and television show characters), which may increase the social acceptability of bisexual identity (Callis, 2014). The elevated smoking rates among sexual minorities coupled with lower access to healthcare (Trinh et al, 2017) lead to an increased risk for negative health consequences (e.g., cancer, respiratory illnesses, cardiovascular diseases) (Blosnich et al, 2013; Caceres et al, 2017). Moreover, tobacco use disparities among sexual minority individuals are likely established in smoking initiation during adolescence and young adulthood (Burkhalter, 2015; Corliss et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are likely a variety of factors influencing this growth, such as the increasing visibility in popular culture of individuals that are neither hetero- nor homosexual (e.g., pop stars and television show characters), which may increase the social acceptability of bisexual identity (Callis, 2014). The elevated smoking rates among sexual minorities coupled with lower access to healthcare (Trinh et al, 2017) lead to an increased risk for negative health consequences (e.g., cancer, respiratory illnesses, cardiovascular diseases) (Blosnich et al, 2013; Caceres et al, 2017). Moreover, tobacco use disparities among sexual minority individuals are likely established in smoking initiation during adolescence and young adulthood (Burkhalter, 2015; Corliss et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With a few exceptions, 55 there is a paucity of research examining racial/ ethnic differences in psychosocial and behavioral risk factors for CVD in SMW. 6 Future studies should use intersectional approaches to examine which subgroups of SMW are most at risk for CVD. We found that Black SMW had higher rates of obesity, hypertension, and diabetes than White SMW.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence of higher car-diometabolic risk in sexual minority women (SMW; e.g., lesbian, bisexual) compared to heterosexual women. SMW have higher rates of poor mental health, [5][6][7][8] tobacco use, 6,[9][10][11] heavy drinking, 6,12,13 obesity, 8,[14][15][16][17][18] and hyperglycemia 15,19 that may predispose them to CVD relative to heterosexual women.…”
Section: Introductionmentioning
confidence: 99%
“…Gay and bisexual men's health has focused primarily on prevention and treatment of sexually transmitted infection such as HIV as a result of the AIDS epidemic of the 1980s and early 1990s. However, gay, bisexual, or men who have sex with men (MSM) are at increased risk of other preventable conditions that have not received the same attention, including a higher incidence of smoking, which leads to an increased risk of cardiovascular disease, as well as lung and other cancers [12]. They also are more likely to experience mental health disorders, such as eating disorders, substance abuse, anxiety, depression, and suicidal ideation than their heterosexual counterparts [7].…”
Section: Lgbt Healthmentioning
confidence: 99%